THE ROLE OF TUBERCULOSIS SANATORIUMS IN THE REHABILITATION OF TUBERCULOSIS IN CHILDREN - Abdumanapova R.K. (Scholar Express Journals, 2023)
The article analyzes the methods of detecting tuberculosis in children. During the analysis of methods for detecting tuberculosis in children and adolescents who have had contact with a tuberculosis patient, only 20-30% of children from the focus of tuberculosis infection are detected during a contact examination. In children living in foci of tuberculosis infection, mainly severe and complicated forms of tuberculosis are detected.
Keywords: Tuberculosis; method of manifestation; children; adolescents